The n-dimensional distributional Mellin transformation - Sunil Kumar Sinha (International Journal of Mathematics and Mathematical Sciences)
The n-dimensional distributional Mellin transformation is developed using the testing function space Mc,d and its dual M′c,d The standard theorems on analyticity, uniqueness and continuity are proved. A necessary and sufficient condition for a function to be an n-dimensional Mellin transformation is proved by the help of a boundedness property for distribution in M′c,d. Some operational transform formulas are also introduced.